Cover Image, Volume 32, Issue 4. (18th March 2019) - Assaf, Yaniv; Johansen‐Berg, Heidi; Thiebaut de Schotten, Michel; Leemans, Alexander
Abstract : The cover image is based on the Special Issue Review Article The role of diffusion MRI in neuroscience by Yaniv Assaf et al., https://doi.org/10.1002/nbm.3762 . Image Credit: Brain Connectivity and Behaviour Laboratory.